A Metaphor Analysis in Kali Uchis’s Territorial Song Lyrics - Delivia Ananda Rizky; Muhammad Alfiyansyah; Savinka Rizki Ramadhani; Yu'anza Reivia (Indo Publishing, 2025)
This study analyzes conceptual metaphors in Kali Uchis's “Territorial” to reveal how metaphors construct themes of romantic possession and self-defense. Using a qualitative descriptive design and Lakoff and Johnson’s (1980) framework, we identified 12 metaphors within the lyrics. The analysis found that ontological metaphors were the most dominant (58.3%), illustrating the reification of abstract emotions. For instance, jealousy materialized as a physical space in “my territory,” and emotional traits were objectified in phrases like “my claws come out.” Structural metaphors (33.3%) framed the relationship as a conflict, mapping concepts of war onto love, as seen in “I’ll go to war about mine.” A single orientational metaphor (8.4%), “gone too far,” spatially evaluated a rival's behavior. The study concludes that these metaphors are not merely decorative but are fundamental cognitive tools that shape the song's narrative, transforming complex feelings of love and jealousy into a coherent and potent discourse on emotional boundaries and autonomy.